What could be the future of hydrothermal processing wet biomass in Germany by 2030? A semi-quantitative system analysis. (July 2020) - Reißmann, Daniel; Thrän, Daniela; Bezama, Alberto
Abstract: The hydrothermal conversion of wet biomass into carbon-rich products is credited with a high potential. But in Germany corresponding large scale facilities have not been established yet. In order to investigate why this is the case, we have identified key factors for the development of hydrothermal processes (HTP) in Germany in previous works. Based on this, this study presents three scenarios of HTP development in Germany by 2030 that represent different combinations of key development factors considering high probability and relevance of occurrence as well as risks in case of factors non-occurrence. Using fuzzy cognitive mapping, connections between the factors are modelled. Further, the system is analysed on its reaction to the scenarios, so that important impacts can be identified. A punctual result is, that for the scenario including most relevant key factors, a normative and economic stabilization of the system is observable. This is above all reasoned in the assumed supporting legal framework. Thus, this path is the most suitable for a successful HTP development in Germany according to this analysis. Highlights: HTP are promising technologies to convert wet biomass into carbon-rich products. In Germany, however, there are no large-scale facilities so far. For future HTP large-scale development legal and technological action is needed. Legal action: The approval of HTP products as standard fuels. Technological action: Promote nutrient recycling and system integrated approaches.